Plexiform schwannoma on the frontal region: a case report - Xiuwen ZHANG; Bingyang YU; Lei SUN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
A case of frontal plexiform schwannoma is reported. A 48-year-old female presented with a 17-year history of a mass on the left frontal region and a 3-year history of a tumor on the left eyebrow arch. Dermatological examination showed an about 8 mm×6 mm×3 mm yellow-red round nodule on the left frontal region. The nodule was firm without tenderness. A subcutaneous mobile nodule in size of about 9 mm×8 mm×4 mm was palpated above the left eyebrow arch, with a firm texture and mild tenderness. The histopathology of both lesions showed multiple tumor masses composed of spindle cells in the middle and lower dermis. Tumor masses were nodular, separated by thin fibrous connective tissue. Immunohistochemistry showed S-100 (+++), Vimentin (+), SMA (-), CD34 (-), and Ki-67 (5%+). A plexiform schwannoma was diagnosed. Surgical resection was performed, and no recurrence was found during a 3-year follow-up.